Mechanisms of Immunopathogenesis in Cutaneous Leishmaniasis And Post Kala-azar Dermal Leishmaniasis (PKDL) - Volpedo, Greta; Pacheco-Fernandez, Thalia; Holcomb, Erin A.; Cipriano, Natalie; Cox, Blake; Satoskar, Abhay R. (Frontiers in Cellular and Infection Microbiology, 2021)
Leishmaniasis is a neglected tropical disease that affects 12 million people worldwide. The disease has high morbidity and mortality rates and is prevalent in over 80 countries, leaving more than 300 million people at risk of infection. Of all of the manifestations of this disease, cutaneous leishmaniasis (CL) is the most common form and it presents as ulcerating skin lesions that can self-heal or become chronic, leading to disfiguring scars. This review focuses on the different pathologies and disease manifestations of CL, as well as their varying degrees of severity. In particular, this review will discuss self-healing localized cutaneous leishmaniasis (LCL), leishmaniasis recidivans (LR), mucocutaneous leishmaniasis (MCL), anergic diffuse cutaneous leishmaniasis (ADCL), disseminated leishmaniasis (DL), and Post Kala-azar Dermal Leishmaniasis (PKDL), which is a cutaneous manifestation observed in some visceral leishmaniasis (VL) patients after successful treatment. The different clinical manifestations of CL are determined by a variety of factors including the species of the parasites and the host’s immune response. Specifically, the balance between the pro and anti-inflammatory mediators plays a vital role in the clinical presentation and outcome of the disease. Depending upon the immune response, Leishmania infection can also transition from one form of the disease to another. In this review, different forms of cutaneous Leishmania infections and their immunology are described.